Construction of the Qur’anic Values as the Basis for Islamic Education Development: A Study of Abdullah Saeed’s Thought - Moh. Muslih (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2020)
The present study aims to elucidate the construction of the values of the Qur’an ​​as the basis for the Islamic education development based on Abdullah Saeed’s thought. The concept of a hierarchy of values initiated by Abdullah Saeed is a continuation of Rahman’s general principles, proposing a new way of looking at the ethico-legal verses in the Qur’an, so that this concept is very pivotal in contemporary Qur’anic studies. Framed in a library research with a content analysis, this study constructed a basic framework from the values ​​of the Qur’an. Abdullah Saeed’s book entitled “Interpreting the Qur’an: Towards a Contemporary Approach” became the primary source in obtaining the data. Study findings reveal that the construction of the Qur’anic values comprises obligatory, fundamental, protective, implementation, and instructional values. The construction ​​can be adopted as the basis for Islamic education development regarding the institution, courses, values ​​and culture. This study also demonstrates that Qur’anic values-based Islamic education is completely projected to produce qualified and competitive human resources in the globalized age.